Tablet of captopril with a cross-linked system of alginate - Sukmadjaja Asyarie; Heni Rachmawati; Pricillia Sinambela (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2007)
Captopril has a short biological half life (1-3h) and has been used for long-term treatment of hypertension. The properties of captopril such as freely water-soluble and instability in intestinal environment lead to the difficulty of developing captopril as a sustained-release preparation. . In this study, sustained-release of captopril was prepared with a matrix system using sodium alginat as a polymeric forming-matrix. The ratio of sodium alginat and captopril was 1:2. Matrix system was obtained by forming alginate cross-linked with a various concentration of calcium acetate. Xanthan gum was used to help cross-linked reaction. Tablet was prepared by wet granulation and the dissolution test was performed in HCl 0.01 N, paddle method, 100 rpm, for 12 h. Although release profile of captopril from all formula developed were different, the release of captopril sustained up 12 h. Formula containing 30 % of xanthan gum and 40 % of sodium alginate showed the best release profile of captopril and the hardness of tablets do not influence to the release of captopril. Tablet of captopril with a crosslinked system of alginate sustained the release of captopril until 12 h .Key words: captopril, sustained-release, sodium alginat, calcium acetat.